Pattern of presentation of idiopathic polypoidal choroidal vasculopathy in Ibadan, Sub-Saharan Africa - Oluleye TS (Dove Medical Press, 2013)
TS Oluleye, Y Babalola Retina and Vitreous Unit, Department of Ophthalmology, University of Ibadan and University College Hospital, Ibadan, Nigeria Background: Idiopathic polypoidal choroidal vasculopathy is an abnormal choroidal vascular pathology similar to age-related macular degeneration. It may present with sudden visual loss from hemorrhagic retinal pigment epithelial detachment and breakthrough vitreous hemorrhage or with chronic recurrent episodes. The condition is not uncommon in the retina clinic at the University College Hospital, Ibadan, Sub-Saharan Africa. This study presents the pattern of presentation in Ibadan. Methods: We review all cases of idiopathic polypoidal choroidal vasculopathy seen from 2007 to 2012 in the retina clinic at the University College Hospital, Ibadan, to determine the major pattern of presentations, available treatment modalities, and visual outcomes. Results: Ten cases were seen during the study period. Their mean age was 58 years, with a male to female ratio of 1:4. The most common presenting complaint was sudden visual loss. Major examination findings were retinal pigment epithelial detachment, orange subretinal lesions, and breakthrough vitreous hemorrhage. The modalities of treatment available included vitrectomy to clear vitreous hemorrhage. Intravitreal bevacizumab reduced the height of the pigment epithelial detachment and cleared vitreous hemorrhage. Thermal laser was applied for extrafoveal lesions. Two patients with subfoveal lesions were referred abroad for photodynamic therapy. Visual outcome showed significant improvement in vitrectomized patients who presented with vitreous hemorrhage. Presenting vision of hand motion and light perception improved to vision ranging from counting fingers to 6/12 after vitrectomy. Conclusion: Idiopathic polypoidal choroidal vasculopathy may not be uncommon in Sub-Saharan Africa. A high index of suspicion is warranted in the diagnosis so as to provide timely intervention. Keywords: idiopathic polypoidal choroidal vasculopathy, retinal pigment epithelial detachment, presentations, Sub-Saharan Africa